Developing “Harmony” (Helping And Resolving Mental Health Issues Online For New You) As A Online Counseling Services In University - Prabowo, Arga Satrio; Nurmala, Meilla Dwi; Rindiyani, Dwi; Mirnawati, Mirnawati (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Developing “Harmony” (Helping And Resolving Mental Health Issues Online For New You) As A Online Counseling Services In University. The results of a mental health survey conducted on 3607 students of Sultan Ageng Tirtayasa University in 2024 showed that more than 70% of students felt the need for counseling services to help them deal with mental health problems. The high number of needs for counseling services makes it necessary for universities to think about other options from the face-to-face counseling services that have been running so far, especially since Sultan Ageng Tirtayasa University has students spread across 5 different campus locations. Online counseling is needed to increase student access to counseling services. This study aims to develop a prototype of a website-based online counseling service. This online counseling service website is called HARMONY. The research method used in this study is the System Development Life Cycle (SDLC) Waterfall. The stages of this research are analysis, design, implementation, testing, and maintenance. In addition to presenting video conferencing features for use in counseling services, this website also includes other features such as mental health assessments, personality character assessments, and interest assessments. With this online counseling service website, students will find it easier to get mental health services.Keywords: Harmony, Online Counseling, Mental Health, University